Complications and Disease Recurrence After Ileocecal Resection in Pediatric Crohn's Disease: A Retrospective Study - Glenisson, M.; Bonnard, A.; Berrebi, D.; Belarbi, N.; Viala, J.; Martinez-Vinson, C. (European Journal of Pediatric Surgery, 2023)
Objective The aim of this retrospective study was to describe the risk of postoperative recurrence (POR) after ileocecal resection, the occurrence of surgical complications, and identify predictors of these adverse postoperative outcomes in pediatric Crohn's disease (CD).Patients and methods All the children less than 18 years of age with a diagnosis of CD, who underwent primary ileocecal resection for CD between January 2006 and December 2016 in our tertiary center, were considered for inclusion. Factors related to POR were investigated.Results A total of 377 children were followed for CD between 2006 and 2016. During this period, 45 (12%) children needed an ileocecal resection. POR was diagnosed in 16% (n = 7) at 1 year and 35% (n = 15) at the end of the follow-up, with a median follow-up of 2.3 years (Q1–Q3 1.8–3.3). Median duration of the postoperative clinical remission was 1.5 years (range 0.5–2). Multivariate Cox regression analysis identified only young age at diagnosis as a risk factor for POR.In total, 7 of the 43 patients (16%) developed severe postoperative complications, defined as requiring surgical, endoscopic, or radiological intervention. The only risk factor was intraoperative abscess.Conclusion Only young age at diagnosis was associated with POR. This information could be useful to develop targeted therapeutic strategies for young CD children. At the end of follow-up with a median follow-up of 2.3 years (Q1–Q3 1.8–3.3), there was no surgical POR: endoscopic dilatation for POR should be considered in order to delay or prevent surgery.
Keywords: Crohn's disease; ileocecal resection; postoperative recurrence